Genetic Counselor Information Needs & Current Library Services for Genetic Counselors - Petty, Elizabeth; Hall, April; Donahue, Amy (My University, 2018)
Genetic counseling is a unique, rapidly growing field with increasingly diverse practice settings. It spans the information-dense world of genomics, precision medicine, and multiple clinical specialties. The purpose of the genetic counseling information needs survey was to gain a broad understanding of the information that genetic counselors and genetic counseling students need in their work and education. Additionally, we explored the resources these individuals use to find information and the barriers that stand in the way of getting information. In the second survey, services and resources currently provided by libraries in support of genetic counseling were captured. The intent is to elucidate gaps between the needed information and existing resources/services. Suggested APA style citation: Donahue, A., Hall, A. & Petty, E. (2018). Genetic counselor information needs & current library services for genetic counselors. [Data file] Retrieved from http://digital.library.wisc.edu/1793/78637
The surveys were administered using the UW-Madison Qualtrics tool, and the results were extracted as CSV files. The files have not been edited in any way. This study (project #2017-1409) was granted exemption by the University of Wisconsin Health Sciences IRB on November 30, 2017 (a change to to the protocol allowing submission of these results to MINDS@UW was granted on 6/15/2018). - The genetic counseling survey asked about information needs using both free form responses to broad scenarios and multiple choice questions about specific situations. It also asked about the use and availability of specific information resources, and about barriers faced in accessing information. Demographic information such as age, race/ethnicity, genetic counseling specialty, type of employment, training program, years practicing, etc. was also collected. Participants were able to save progress and return to the survey. The online survey was sent through national listservs via email to genetic counselors who are members of the National Society of Genetic Counselors (NSGC) and/or the American Board of Genetic Counselors (ABGC). The same genetic counseling online survey was sent via email to the Association of Genetic Counseling Program Directors (AGCPD) listserv, requesting that the directors forward the survey to students in their programs. - The library survey asked about whether the library serves genetic counselors and/or genetic counseling students. The bulk of the survey included questions about specific resources (journals, books, databases, etc.) and services (educational sessions, literature searching, etc.) provided specifically to genetic counselors. Demographic information, including the type of setting, the region of the country, number of library employees, and size of the home organization was also collected. Participants were able to save progress and return to the survey, and no questions are required. The library online survey was sent through national listservs via email to members of the Medical Library Association (MLA) and/or members of the National Network of Libraries of Medicine. Participants were instructed to submit only one response per library setting.
Keywords: library; library services; information behavior; information needs; genetic counselors; genetic counseling